If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 0.25(200) = X Multiply 0.25 * 200 10 + 50 = X Combine like terms: 10 + 50 = 60 60 = X Solving 60 = X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1X' to each side of the equation. 60 + -1X = X + -1X Combine like terms: X + -1X = 0 60 + -1X = 0 Add '-60' to each side of the equation. 60 + -60 + -1X = 0 + -60 Combine like terms: 60 + -60 = 0 0 + -1X = 0 + -60 -1X = 0 + -60 Combine like terms: 0 + -60 = -60 -1X = -60 Divide each side by '-1'. X = 60 Simplifying X = 60
| 8+7m=m-4 | | 10-(x-7)+2x=5 | | r^2-3=2r | | 2=-2b-8 | | -17+3(.25)=x | | 6n-3=4+5n | | 4g=5 | | X^2+5x-24=-6+2x | | 10+X=-30 | | (X+6)(X-8)(2x-7)=0 | | -8(t+9)=6 | | 3x-1+4x+3=180 | | 5b^2+31b+30=0 | | y^2-4x^2=16 | | 6=7s-4 | | 2+2p=2-2p | | 1.82=Log(x) | | 2(-4)-3=x | | 5x+4=6x-42+8 | | 7+m=6 | | 2p+4p-7x+3=4p+5-3x | | -5x-6=-1 | | V^2-2v-5=-3v-3 | | 12x-8=15x-14 | | -5(x-3)=5(x-3) | | 5m+3n-2m-8n= | | (x+2)(7x+8)=0 | | 9-4+5h+3x= | | 9x/2=3x | | 9-4+53+32= | | 25c^2-121g^2=0 | | Y=3/4x-9;(-8,-18) |